Fear of Missing Out as a Moderator of Financial Literacy and Generation Z Investment Decisions in Cirebon - Hanifah Hana Dewi Khoirunnisa; Nuhana Dhea Parlina (Danadyaksa: Post Modern Economy Journal, 2026)
Digital investment platforms have expanded investment access among Generation Z, but easier access does not always ensure rational investment decisions. This study examines the effect of financial literacy on investment decisions among Generation Z in Cirebon and analyzes the moderating role of fear of missing out in this relationship. A quantitative associative design was applied using survey data collected from 105 respondents selected through purposive sampling. The respondents were Generation Z individuals aged 17–28 years who lived in Cirebon and had investment experience or interest. Data were analyzed using partial least squares structural equation modeling. The findings show that financial literacy has a positive and significant effect on investment decisions, indicating that better financial understanding improves the ability of young investors to evaluate risk, return, and investment alternatives. Fear of missing out also has a positive and significant effect on investment decisions, suggesting that psychological and social pressure can encourage investment participation. More importantly, fear of missing out negatively moderates the relationship between financial literacy and investment decisions, meaning that high fear of missing out weakens the role of financial literacy in guiding rational investment decisions. This study contributes to behavioral finance literature by integrating rational and psychological factors in explaining young investors’ behavior and provides practical implications for investment literacy programs that include behavioral awareness.